Strategies Used by Microentrepreneurs to Develop Their Businesses in the Sipiso-Piso Tourist Area - Diana Derlina Ndruru; Menanti Br Sembiring; Benni Purba (Indonesian Journal of Advanced Research, 2026)
This study aims to analyze the strategies used by micro-business owners in developing their businesses in the Sipiso-Piso tourist area, Karo Regency, North Sumatra. The concepts examined include strategies related to human resources, capital, products, and marketing. The study employs a descriptive qualitative approach, using data collection techniques such as interviews, observations, and documentation of micro-entrepreneurs in the culinary, souvenir, and lodging sectors during the research period. The results indicate that business development is achieved through the utilization of local labor, self-financing, product quality improvement, and promotion—both in person and via digital media. Consequently, strengthening human resources, improving access to capital, fostering product innovation, and enhancing digital marketing are necessary to support the sustainability of microenterprises in the tourism area.